Tsunami Simulation in Paseban Beach Using Nesting Method on Delft3D Modeling - Faradella, Maulida; Wiyono, Retno Utami Agung; Halik, Gusfan (Rekayasa Sipil, 2024)
Paseban Beach is an area that has the potential for a tsunami hazard. In analyzing the tsunami hazard, accurate data and methods are essential. Therefore, this study aims to conduct a tsunami hazard analysis using the nesting method to obtain precise modeling results. This study utilizes the Delftdashboard and Delft3D-Flow programs. The modeling of the 1994 Banyuwangi tsunami results show that the validation stage has an accuracy of 7.94%, which means it is very accurate. The tsunami modeling using the 8.7 Mw megathrust earthquake showed the tsunami wave height in Paseban Beach reached 10,25 meters with 46 minutes arrival time. The length of the tsunami inundation was measured to be 2.96 km, with a run-up height of 2.98 meters.